Implementation of the Project for Strengthening the Profile of Pancasila Students (P5) in the Independent Curriculum at SDN Grinting 01 - Dewi Ana Putri; Moh Toharudin; Novi Yuliyanti (Journal of Education Technology Information Social Sciences and Health, 2024)
This research aims to present a general overview of the project to strengthen the profile of Pancasila students at SDN Grinting 01 class II, along with an analysis of the components and stages that support and hinder the implementation of the project. The research design used was exploratory qualitative. Class II students at SDN Grinting 01, instructors and principals were the subjects of this research. Documentation, interviews, and observation are the three methods used to collect data. The Strengthening Pancasila Student Profile (P5) project has been implemented and is functioning effectively in accordance with its objectives, according to research results. The theme of the P5 curriculum in class II is "Local Wisdom". supporting components. School Principals, Teachers, Parents and the surrounding community are among the parties who support the Strengthening Pancasila Student Profile (P5) Project, providing assistance in its implementation. Teachers' ignorance of the Independent Curriculum and the lack of information and competency training are obstacles in implementing the Strengthening Pancasila Student Profile (P5) Project, even though P5 is a fairly significant advance in the field of education.